Substitution effect of Undaria pinnatifida with citrus (Citrus unshiu, Marcovitch) peel by‐product in feed on the growth, body composition and air exposure stressor of juvenile abalone (Haliotis discus, Reeve 1846). (7th November 2019) - Yun, Ahyeong; Lee, Ki Wook; Kim, Pil Youn; Jeong, Hae Seung; Kim, Hee Sung; Cho, Sung Hwoan; Kim, Taeho
Abstract: Substitution effect of Undaria pinnatifida with citrus peel by‐product (CPB) on growth, body composition and air exposure stressor of abalone was determined. A total of 1, 080 abalone were distributed into 18 net cages. Five formulated diets were prepared in triplicate. The CPB0 diet contained 200 g/kg U .  pinnatifida . The 250, 500, 750 and 1, 000 g/kg U. pinnatifida were substituted with the equal amount of CPB, referred to as the CPB250, CPB500, CPB750 and CPB1000 diets, respectively. Finally, dry U. pinnatifida was prepared. Abalone were fed for 16 weeks and then subjected to air exposure stressor for 24 hr. The cumulative mortality of abalone was monitored for the following 4 days after 24‐hr air exposure. Survival, weight gain and specific growth rate (SGR) of abalone fed all formulated diets were greater than those of abalone fed the U. pinnatifida . The greatest weight gain and SGR were achieved in abalone fed the CPB500 diet. The chemical composition of the soft body of abalone was not affected by the experimental diets. Higher cumulative mortality was observed in abalone fed the CPB0 and dry U .  pinnatifida at 16 hr after 24‐hr air exposure compared to abalone fed all other diets. In conclusion, U. pinnatifida could be completely substituted with CPB in abalone feed.